Power phone scripts : 500 word-for-word questions, phrases, and conversations to open and close more sales - Brooks, Mike, 1957- (Business professional collection, 2017)
Actionable, fun, and designed to work within the current sales environment, this invaluable guide provides proven, current, and word-for-word phrases, rebuttals, questions, and conversation openers that will instantly make you sound more confident so you get that next sale. --